2015
DOI: 10.1016/j.jvs.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of symmetric dimethyl-arginine are associated with all-cause mortality in patients with symptomatic peripheral arterial disease

Abstract: The novel finding of this study is that SDMA levels were predictive of all cause-mortality and correlated with disease severity. Further studies should assess the role of nitric oxide donors in patients with high levels of SDMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…A total of 2119 patients were investigated comprising both inpatients and outpatients with lower extremity PAD. All-cause mortality was increased with high ADMA levels (HR, 2.23; P =0.024 50 and HR, 1.31; P =0.037). 51 MACE was also increased in patients with higher levels of ADMA (HR, 5.2; P <0.001 52 and HR, 1.70; P =0.043).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…A total of 2119 patients were investigated comprising both inpatients and outpatients with lower extremity PAD. All-cause mortality was increased with high ADMA levels (HR, 2.23; P =0.024 50 and HR, 1.31; P =0.037). 51 MACE was also increased in patients with higher levels of ADMA (HR, 5.2; P <0.001 52 and HR, 1.70; P =0.043).…”
Section: Resultsmentioning
confidence: 98%
“…The 47 included studies were sorted per biomarker; several studies appeared in different groups as they investigated multiple biomarkers. The following biomarkers were studied: 13 studies investigated high-sensitivity CRP (hs-CRP), 11 , 14 26 2 reported on GDF-15 (growth differentiation factor 15), 14 , 27 2 on MPO (myeloperoxidase), 24 , 28 6 on the neutrophil-lymphocyte ratio (NLR), 29 34 2 assessed SAA (serum amyloid A), 22 , 35 6 reported on fibrinogen, 19 , 35 39 another 7 assessed d -dimer, 22 , 25 , 38 , 40 43 7 investigated NT-proBNP, 11 , 15 , 17 , 44 47 5 hs-cTnT, 10 , 44 , 45 , 48 , 49 4 asymmetrical dimethylarginine (ADMA), 50 53 4 assessed adiponectin, 54 57 and 3 homocysteine. 18 , 22 , 58 Investigated outcomes were heterogenous across studies but mainly included all-cause mortality, cardiovascular mortality, cardiovascular events, major adverse cardiovascular events (MACE), major adverse limb events, coronary events, amputation-free survival, amputation, reintervention for lower extremity PAD, and graft patency.…”
Section: Resultsmentioning
confidence: 99%
“…Increased circulating ADMA levels have been predictive of fatal and nonfatal cardiovascular events in at‐risk populations . SDMA was an independent predictor of all‐cause and cardiovascular mortality in the general population in a large multi‐ethnic cohort study and with all‐cause mortality in patients with symptomatic peripheral arterial disease …”
Section: Underlying Mechanisms Contributing To the Antihypertensive Ementioning
confidence: 97%
“…The remaining 14 studies underwent fulltext review, and eight studies were further excluded because two studies were not relevant studies to the current meta-analysis, one was not prospective cohort study, four did not report the outcome of interest, and the other one was not performed in patients with PAD. Finally, six prospective cohort studies 9,[16][17][18][19][20] were included in the present meta-analysis.…”
Section: Searching Resultsmentioning
confidence: 99%
“…16 However, inconsistent results were retrieved regarding the prognostic role of circulating ADMA at baseline in patients with PAD. 9,[16][17][18][19][20] Therefore, in study, we aimed to quantitatively evaluate the prognostic efficacy of circulating ADMA for cardiovascular outcome in patients with PAD by combining available evidence in a meta-analysis.…”
Section: Introductionmentioning
confidence: 99%